Pengaruh Aromaterapi Lavender Untuk Mengurangi Dismenore Pada Remaja Putri : Systematic Literatur Review - Zelvia Barreto; Evy Ernawati; Febry Heldayasari Prabandari (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: Primary dysmenorrhea occurs due to an increase in prostaglandin (PG) F2-alpha resulting in hypertonus and vasoconstriction in the myometrium resulting in ischemia and pain in the lower abdomen. The existence of strong and long contractions in the uterine wall, high prostaglandin hormones and widening of the uterine wall when removing menstrual blood so that there is pain during menstruation. According to the World Health Organization (WHO) the incidence of dysmenorrhea is quite high throughout the world. In young women 16.8-81%, Europe 45-97%, the highest prevalence in Finland is 94%, the lowest is in Bulgaria 8.8%, a survey conducted in the United States 29-44% mostly at the age of 18-45 year. In Indonesia 64.25%. Purposes: To determine the effect of lavender aromatherapy to reduce dysmenorrhea in adolescent girls. Research Methods: This study uses the Systematic Literature Review (SLR) method. Using a sample of 13 international and national journals using data based on Cochrene, Google scholar, and NCBI. Results: This study showed results of 100 % (13 journals) decreased pain scale after offering lavender aromatherapy. The cause of dysmenorrhea based on journals is age (61.5%), menarche age 13 years (46.1%) regular cycle (76.9%), menstrual length 2-6 days (69.2%). The pain scale based on the journal is moderate pain (77%), and the intervention given is based on the journal, namely inhalation (53.8). Conclusion: There is an effect of lavender aromatherapy to reduce dysmenorrhea in young women.